Seawater carbonate chemistry and germling growth rate, and male and female gametophyte sizes of kelps Macrocystis pyrifera and Undaria pinnatifida in laboratory experiment - Leal, Pablo P; Hurd, Catriona L; Fernández, Pamela A; Roleda, Michael Y (Supplement to: Leal, PP et al. (2016): Meiospore development of the kelps Macrocystis pyrifera and Undaria pinnatifida under ocean acidification and ocean warming: independent effects are more important than their interaction. Marine Biology, 164(1), https://doi.org/10.1007/s00227-016-3039-z, 2017)
Anthropogenic atmospheric emissions of CO2 are responsible for simultaneous ocean warming (OW) and ocean acidification (OA). These global events can have important impacts on marine fleshy macroalgae and coastal ecosystems. To understand the effects of OW and OA on the early life history stages of native (Macrocystis pyrifera) and invasive (Undaria pinnatifida) macroalgae, a multi-factorial experiment was performed to determine the independent and interactive effects of the drivers and the corresponding species-specific responses. Meiospores of M. pyrifera and U. pinnatifida were separately exposed to a 4 * 2 factorial design of seawater pH (pHT 7.20, extreme OA predicted for 2300; pHT 7.65, OA predicted for 2100; pHT 8.03, ambient pH; and pHT 8.40, pre-industrial pH) and temperature (12 °C, seasonal average temperature; and 16 °C, OW predicted for 2100). Over 15 days, different physiological parameters (i.e. meiospore germination, germling growth rate, gametophyte development and sex ratio) were measured. Reduced seawater pH and elevated temperature had independent and significant effects on developmental processes (germling growth rate, and male and female gametophyte sizes were independently greater under OA and OW conditions), but the interaction of the abiotic factors had no effect on any stage of meiospore development of either species. Despite some small differences between species (e.g. sex ratio), results of this experiment suggest that microscopic stages of the native M. pyrifera and the invasive U. pinnatifida will respond similarly to OA and OW.
Keywords: Benthos; Bottles or small containers/Aquaria (<20 L); Chromista; Coast and continental shelf; Laboratory experiment; Macroalgae; Macrocystis pyrifera; Ochrophyta; Reproduction; Single species; South Pacific; Temperate; Undaria pinnatifida